Kajian Yuridis Penggunaan Dana Pribadi Presiden dalam Pembiayaan Perjalanan Dinas Ditinjau dari Asas Akuntabilitas Keuangan Negara - Komang Arta Jutawan; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku; Gusti Ayu Apsari Hadi; I Gusti Ngurah Budiyasa (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
The President’s use of personal funds to finance official state trips has sparked debate from the perspective of public finance law because it is carried out outside the mechanisms of the State Revenue and Expenditure Budget (APBN), which serves as the basis for the management of state finances. This study aims to analyze the legal implications of the President’s use of personal funds on the fulfillment of the principle of state finansial accountability and to provide an ideal solution in accordance with the provisions of applicable laws and regulations. This study is a normative legal study employing a statutory approach and a conceptual approach. Legal materials were obtained through a literature review and analyzed using a descriptive-qualitative methodology based on deductive reasoning. The results of the study indicate that the President’s use of personal funds to finance official travel has the potential to be inconsistent with the principle of accountability and the oversight and audit mechanisms of the State Audit Agency. This practice also has the potential to create legal uncertainty regarding the recording and accountability of state finances. Therefore, the financing of the President’s official travel should continue to be carried out through mechanisms available within the state financial system or by revising the Budget Implementation Form (DIPA), the Revised State Budget (APBN Perubahan), or through legitimate grant mechanisms, so that the principle of accountability in the management of state finances is upheld.